Heavy metal(loid)s in fruit-growing soil of tropical Hainan Island in China: Pollution, ecological-health risks, spatial assessment, and source analyses - Wu, Xiaofang; Zhou, Cailin; Xie, Yi; Wang, Xiaogang; Deng, Aini (International Journal of Agricultural and Biological Engineering, 2023)
Hainan  Island  is  the  most  important  tropical  fruit  production  area  in  China.  In  this  study,  372  soil  samples  andcorresponding  fruit  and  irrigation  water  samples  were  collected  from  Hainan  orchards  and  analysed  to  determine  theconcentrations of six heavy metal(loid)s: Cd, Hg, As, Pb, Cr, and Cu. The pollution status, potential risks, possible sources, andspatial  distribution  patterns  of  soil  heavy  metal(loid)s  were  comprehensively  investigated.  The  fruit  and  irrigation  watersamples had negligible amounts of heavy metal(loid)s, and the potential human health risk for fruit consumers was at a safelevel. The heavy metal(loid) concentrations in most soil samples were lower than the national risk screening values. However,significant  local  accumulation  of  heavy  metal(loid)s,  especially  Cd,  Cr,  and  Cu,  relative  to  their  background  values  wasobserved. Moreover, the combined effects of the heavy metal(loid)s only led to a mild pollution level and low ecological riskthroughout the study area. Noncarcinogenic risks were not observed among the local residents, and carcinogenic risks werewithin an acceptable range. The acidic soil in the study area increased the risk of soil Cd pollution, and organic matter affectedthe  distribution  of  the  tested  metal(loid)s  in  the  soil.  Uncommon  geogenic  sources  with  high  background  values  were  thesources  of  Cr  and  Cu,  anthropogenic  activities  primarily  led  to  Cd,  Pb,  and  As  contamination,  and  a  combination  ofanthropogenic and natural sources was responsible for Hg emissions. The research suggested that appropriate strategies must beimplemented to track and reduce soil heavy metal contaminants in the northern and western region of the Hainan orchard area.The  results  can  provide  valuable  information  for  policies  on  pollution  prevention  and  management,  the  environment,  andhuman health protection in the study region.Keywords: heavy  metal(loid)s, Hainan  Island, orchard, pollution  assessment, ecological-health  risk  assessments, spatialdistribution, source analysisDOI: 10.25165/j.ijabe.20231604.8011Citation: Wu X F, Zhou C L, Xie Y, Wang X G, Deng A N. Heavy metal(loid)s in fruit-growing soils of tropical Hainan Islandin China: Pollution, ecological-health risks, spatial assessment, and source analyses. Int J Agric & Biol Eng, 2023; 16(4): 231–244.